Perempuan dalam Hukum Keluarga Islam: Pandangan Progresif Jamal Al-Banna - Royan Utsany (BUANA GENDER : Jurnal Studi Gender dan Anak, 2017)
The practice of marginalization and subordination is found in many family law provisions produced by jurists. Jamal Al-Banna is an Egyptian thinker who has an interest in women's issues. Through his work, Al-mar'ah Al-Muslimah baina Tahrir Alquran wa Taqyid Al-Fuqaha ', Jamal tries to point out the fact that in practice, the jurists have performed shackles/restrictions (taqyid) against women. This research method using descriptive qualitative. The results of this study indicate that Jamal's thought in his work explains the Qur'an in fact actually gives freedom (tahrir) is full of women. With the starting point of the Qur'an, Jamal began his new things. Jamal seeks to reform the position of women in social structure, For Jamal, social reform can only be done by reconstructing the religious understanding of the smallest institution called family.